2000
DOI: 10.1053/rapm.2000.8935
|View full text |Cite
|
Sign up to set email alerts
|

Spread of injectate during C6 stellate ganglion block and fascial arrangement in the prevertebral region: An experimental study using donated cadavers

Abstract: These results suggest that the PVILS plays a critical role in the spread of injectate as well as being a potential pathway to the stellate ganglion during SGB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
16
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 17 publications
1
16
0
Order By: Relevance
“…We added contrast material to the anesthetic to identify the spread of solution with CT after injection. Our studies have shown that injection of anesthetic anterior to the prevertebral fascia results in the typical anterolateral spread described by Honma et al and the type I spread pattern of Hogan et al 1,7 This type of spread was also identified by Christie and Martinez. 10 Despite the fact that the majority of solution is extending anterolaterally, contrast material was seen to spread posteriorly to the expected location of the stellate ganglion.…”
supporting
confidence: 82%
See 1 more Smart Citation
“…We added contrast material to the anesthetic to identify the spread of solution with CT after injection. Our studies have shown that injection of anesthetic anterior to the prevertebral fascia results in the typical anterolateral spread described by Honma et al and the type I spread pattern of Hogan et al 1,7 This type of spread was also identified by Christie and Martinez. 10 Despite the fact that the majority of solution is extending anterolaterally, contrast material was seen to spread posteriorly to the expected location of the stellate ganglion.…”
supporting
confidence: 82%
“…However, one cannot have a thoracic sympathetic block from an anterior C6 approach without affecting the cervical sympathetic chain and the SG. In fact, this type of associated thoracic sympathetic block would be unusual given the usual spread patterns described by Honma et al 1 and Hogan et al 7 following the anterior C6 approach.…”
mentioning
confidence: 76%
“…Horner's syndrome is frequently reported in interscalene or supraclavicular block [21][22][23] and may correspond to a diffusion of anesthetics in prevertebral spaces ultimately involving the sympathetic nerves and communicating with cervical nerve trunks. 24 In conclusion, the infraclavicular approach offers an alternative to the axillary approach, especially when movement of the patient's arm is not possible. The rate of success with this approach is 89%, and we believe the intercostobrachial nerve block should be added for surgical procedures requiring a tourniquet.…”
Section: Discussionmentioning
confidence: 96%
“…However, the alar fascia concept displays gradual changes depending on the researchers. Honma et al (2000), in a study demonstrating that injectates of C6 stellate ganglion block travel through the prevertebral interlaminar space or danger space between the alar fascia and prevertebral lamina of the cervical fasciae, described a meso-like fascia connecting the carotid sheath and alar fascia. Thus, as seen in Hollinshead (1982; Fig.…”
Section: Discussionmentioning
confidence: 99%
“…6C), Honma et al (2000) considered the alar fascia as part of the prevertebral laminae rather than an ''ala'' (i.e., wing) of the carotid sheath. A concept that the alar fascia connects the bilateral sheathes might be based on a frequent adhesion between the visceral fascia and common sheath (see above) because the retropharyngeal fascia (a part of the visceral fascia) and alar fascia have often been confused in literatures (reviewed in Honma et al, 2000) Grodinsky and Holyoke (1938) designated ''space 3A'' for the potential space within the carotid sheath. Injected materials were usually limited in the space according to injection studies into the space, but sometimes extended through the sheath or wall of the space to cause leakage into the posterolateral and/or visceral spaces.…”
Section: Discussionmentioning
confidence: 99%